Shoulder Capsular Surgery in Finland Between 1999 and 2008: A Nationwide Register Analysis. (June 2018) - Kavaja, L.; Malmivaara, A.; Lähdeoja, T.; Remes, V.; Sund, R.; Paavola, M.
Background and Aims: Shoulder capsular surgery is nowadays usually performed arthroscopically, and the proportion of arthroscopic method has rapidly increased during the last two decades. We assessed the incidence of shoulder capsular surgery procedures in Finland between 1999 and 2008. Material and Methods: We gathered the shoulder capsular surgery procedures for all kinds of shoulder instability in Finland between 1999 and 2008 from National Hospital Discharge Register and limited the patient material to include only certain diagnosis (International Classification of Diseases, 10th Edition) and Nordic Medico-Statistical Committee procedure code combinations. We analyzed the data in the whole country, between different age groups, and in university hospital districts. Results: The total incidence of shoulder capsular surgery procedures in Finland increased from 17 to 33 per 100, 000 person-years. The incidence of arthroscopic procedures increased from 11 to 30 per 100, 000 person-years and the proportion of arthroscopic procedures increased from 63% to 92% between years 1999 and 2007. The incidence of shoulder capsular surgery procedures increased on average around 90% in almost all age groups and particularly in the older age groups. We observed no significant geographical variation between university hospital districts. Conclusion: The incidence of shoulder capsular surgery procedures increased on average round 90% in almost all age groups. It seems to be difficult to support the rapidly increased rates of shoulder capsular surgery procedures or the arthroscopic method based on scientific evidence. While also older patients are treated with shoulder capsular surgery, well-defined indications for surgical intervention are needed so that the operations are conducted for the symptomatic patients benefitting most regardless of patients' age.